Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 10 - Radical Expressions and Equations - 10-4 Solving Radical Equations - Lesson Check - Page 623: 3



Work Step by Step

$Given,$$\sqrt (2x-1)=x$ Squaring both sides, we get: $2x-1=x^{2}$ $Thus,(-2x+1)+2x-1=x^{2}+(-2x+1)$ $x^{2}-2x+1=0$ $(x-1)^{2}=0$ $x-1=0$ $x=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.